Case reportThromboembolic events following brachytherapy: case reports - Guy, Jean-Baptiste; Falk, Alexander Tuan; Chargari, Cyrus; Bertoletti, Laurent; Magné, Nicolas (Journal of Contemporary Brachytherapy, 2015)
Pulsed-dose-rate (PDR) brachytherapy is a recent brachytherapy modality combining the radiobiological advantages of low-dose-rate (LDR) brachytherapy with increased possibilities of dose optimization and radiation safety. However, treatment duration remains protracted, as the prescribed dose is typically delivered through pulses that do not exceed 0.5 Gy/h for critical organs. It is frequently used for the treatment of gynaecological malignancies. Although, the relationship between thrombosis and cancer is well known, specific data on thromboembolic events during brachytherapy are scarce. We report two cases of major thromboembolic events during brachytherapy treatment for gynaecological malignancies. We discuss the possible causal relationship between brachytherapy procedures and the occurrence of thromboembolic events, drawing a preventive practical attitude.